Implementação de uma ferramenta de cálculo de tempos de processo - Luís Carlos Gonçalves Oliveira (2020)
This document shows the work developed within the scope of the Dissertation Project, for the conclusion of the Integrated Masters in Electrical and Computer Engineering (MIEEC) at the Faculty of Engineering of the University of Porto (FEUP), held at ATEP - Amkor Technology Portugal, an industrial company in the semiconductors encapsulation and testing market. This dissertation arises from the ATEP's need to implement a tool that allows its employees to obtain the machine rates, as well as to supervise the entire production line more efficiently, ensuring better capacity planning and production allocation. The work carried out during this dissertation focuses on the creation of models that allow processing the bulk data from the factory, obtaining the rates from the factory's systems, the project focuses on the Wet zone of the production line. During this project, in order to guarantee an efficient solution, it was necessary to comply with several steps, all of which are documented in this report. Initially, an in-depth study of the logic behind the production process and the systems used to extract data from the manufacturing line was carried out. Based on this information, the tool requirements were specified and dialogues were initiated with process engineers in order to obtain detailed information about the machines to be modularized and how they work. Once all the necessary information was gathered, the models for the new tool were created and the respective results were presented. Finally, the models specification was made so the IT Department could develop the code that will implement them in the final tool. The models created during this dissertation have much more accurate results than the methods currently implemented in the company. Once the tool is implemented it will allow major improvements in capacity planning and factory supervision.